Follicular tissue fragments in fine‐needle aspiration cytology of lymph nodes: A useful clue in differential diagnosis of follicular lymphoma and reactive follicular hyperplasia. Issue 7 (20th April 2021) - Sasaki, Yosuke; Kishimoto, Koji; Homma, Mayumi; Shiozawa, Eisuke; Takimoto, Masafumi; Yamochi‐Onizuka, Toshiko
Abstract: Background: In Fine‐needle aspiration cytology (FNAC) of lymph nodes, tissue fragments derived from follicular structures may be observed in specimens. We defined such tissue fragments as follicular tissue fragments (FTF), and investigated differences in cytological findings for FTFs of each histological type. Method: A total of 41 cases with FNAC of lymph nodes were examined. In these cases, the histopathological diagnoses were reactive lymphoid hyperplasia (RLH) (n = 17), follicular lymphoma (FL) (n = 13), diffuse large B‐cell lymphoma (DLBCL) (n = 18), and Burkitt lymphoma (n = 1). Specimens were analyzed for the presence of FTFs, and for tingible‐body macrophages (TBMs) and monomorphism of lymphocytes in FTFs. FTFs with a maximum diameter of >500 μm were defined as large‐FTFs. Results: FTFs were identified in RLH (14/17, 82.4%), FL (13/13, 100%), and DLBCL (3/18, 16.7%). In the RLH subtypes, FTFs were present only in follicular hyperplasia (FH) (14/15, 93.3%) and not in paracortical hyperplasia (0/2). The number of cases with large FTFs among those with FTFs were as follows: RLH (10/14, 71.4%), FL (11/13, 84.6%), and DLBCL (0/3). Similarly, those with TBMs in FTFs were as follows: RLH (13/14, 92.9%), FL (0/13) and DLBCL (2/3, 66.7%). Monomorphism was observed in RLH (1/14, 7.1%) and FL (11/13, 84.6%), but not in DLBCL (0/3). Conclusions: Distinction between FL and FH is possible by identifying large‐FTFs. In FL, TBMs are absent in FTFs and lymphocytes often show monomorphism. Therefore, recognizing FTFs and observing details inside the FTFs are useful for identification and differential diagnosis of FL and FH in FNAC of lymph nodes.